Key elements of social theory revolutionized by Marx - Zarembka, Paul (Studies in critical social sciences, 2020)
"Marx's oeuvre is vast but there are key elements of his ever evolving, class-based contribution to social theory. Declining usefulness for him of Hegelian philosophy and his deepening confrontation with Ricardian political economy were expressions. While the French edition of Capital is closest to Marx's mature thought, Engels did not understand how work on Russia related to Marx's evolution, and Engels distorted the outcome. Accumulation of capital is particularly difficult conceptually, including use of 'primitive accumulation', and is carefully addressed, as is composition of capital. After Marx, Luxemburg is the most significant contributor to Marxism and her works on political economy and on nationalism are highlighted here. The modern topic of state conspiracies, too often avoided, concludes the book. Troubling issues, however, remain"--